Comparing adolescent and service provider perceptions on the barriers to mental health service use: A sequential mixed methods approach. (August 2020) - Platell, Monique; Martin, Karen; Fisher, Colleen; Cook, Angus
Highlights: Novel sequential mixed methods approach. Integration analysis compared adolescent and mental health provider experiences. Strong consensus across samples on the barriers to mental health care. Identified six themes central to adolescent mental health service access and use. Abstract: Background: The rates of young people reporting psychological distress in Australia is increasing but service access by this group remains poor. Many young people are not seeking help for mental health concerns despite often being aware that they may need to. This issue is compounded by the complex nature of barriers that adolescents face when accessing and engaging with mental health services. This paper presents the integrated findings of a three phase mixed methods approach exploring the determinants of mental health service access and use by adolescents in Perth, Western Australia. This research sought to identify the barriers and facilitators experienced by adolescents during mental health help-seeking. This was done by highlighting and comparing the real-world experiences of adolescent mental health consumers at varying points of the help-seeking process with those of professionals providing mental health services. Methods: The overarching study utilised a sequential mixed methods approach comprising of three phases. Each phase investigated its own discrete population: (Phase 1) mental health professionals and clinicians providing services to adolescents; (Phase 2) adolescents aged 14–18 years who intended to seek help for their mental health but had either not yet done so or had discontinued treatment, and; (Phase 3) adolescents aged 14–18 years who were currently using a mental health service or had previously used a mental health service in the past 24 months. Phases 1 and 3 used qualitative interviews, and phase 2 comprised an online survey. The findings of all three phases were then integrated. Equal weighting was given to the qualitative and quantitative results. Results: Six main themes emerged from the integration of findings relating to the determinants for adolescent mental health service access and use: (1) Service entry criteria and intake processes; (2) Invalidating experiences; (3) Mental health system resourcing and service provision; (4) Service features (environment and location etc.); (5) Additional support, and; (6) Client-centred approach to care. Conclusions: A strong consensus between sample groups on the determinants influencing adolescent mental health service access and use was evident in this study. The alignment of views emphasises the importance of the identified themes and highlights how gaps in mental health service provision are experienced by differing stakeholders. The identified themes provide practical areas of focus for future mental health reform.